EVALUATION THE EXPRESSION OF THREE GENES TO EPITHELIAL OVARIAN CANCER RISK IN CHINESE POPULATION - Huang, Ju; Lin, Hao; Lin, Ming En (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Ovarian cancer is associated with poor survival, because patients are diagnosed at an advanced stage of the disease, and in addition, tumors develop chemoresistance, which carries a poor prognosis for the patient. Material and methods: We hypothesize that high expression of SDF-1, survivin and smac is associated with ovarian cancers development and could be used as a biomarker to identify this disease. The expressions of SDF-1, survivin and smac in normal ovarian (NO) tissue, benign tumor (BT) tissue and epithelial ovarian cancer (EOC) tissue were immunohistochemically analysed. Results: Positive expressions of SDF-1, survivin and smac were significantly higher in EOC tissue than those in NO and BT tissues. SDF-1 expressions were significantly more weaker in advanced ovarian carcinomas (FIGO stage III–IV), and in high-grade carcinomas. There was a positive correlation between EOC patients with lymph node metastasis and with ascites and SDF-1 positivity (P < 0.05). Survivin expressions were significantly more stronger in advanced ovarian carcinomas (FIGO stage III–IV), and in high-grade carcinomas. There was a positive correlation between EOC patients with lymph node metastasis and with ascites and surviving positivity (P < 0.05). Smac expressions were significantly more stronger in advanced ovarian carcinomas (FIGO stage III–IV), and in high-grade carcinomas. There was a positive correlation between EOC patients with lymph node metastasis and with ascites and smac positivity (P < 0.05).